Analisis Kaidah Fiqhiyyah Bab Nikah Muharramat Menurut Mazhab Imam Hanafi - Sinulingga, Achmad Yazid; Firmansyah , Heri; Adly , M Amar (Kampus Akademik Publiser, 2024)
This article aims to find out about the rules regarding women who are forbidden to marry, what are the arguments and origins of the rules, what are examples of rules in the application of Islamic family law, what are the exceptions to the rules, and what laws relate to women who are forbidden to marry. This research is normative juridical research, therefore this research is of a legal nature in secondary data research which includes primary materials, namely binding legal materials consisting of statutory regulations, secondary materials which provide explanations of primary legal materials and tertiary materials, namely legal materials which provide explanations of primary and secondary legal materials, including electronic media, dictionaries and so on. The results of this research show that there is a prohibition on the marriage of a man with two women who are sisters. If viewed from the perspective of Islamic law and statutory regulations, the marriage is invalidated.